PENGARUH USER-GENERATED CONTENT DAN SOCIAL MEDIA ENGAGEMENT TERHADAP KEPUTUSAN PEMBELIAN PADA MAHASISWA JURUSAN MANAJEMEN FEB UHO - Dzulfikri Azis Muthalib (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2026)
This study aims to examine the effect of user-generated content and social media engagement on purchase decisions among students of the Management Department, Faculty of Economics and Business, Halu Oleo University. A quantitative approach with an explanatory survey design was employed. Data were collected from 100 active students who had made online purchases influenced by social media content, selected through purposive sampling. Data were gathered using a structured questionnaire, and the research instrument was tested for validity and reliability prior to further analysis. Hypotheses were tested using multiple linear regression analysis with the assistance of SPSS software. The results show that both user-generated content and social media engagement have a positive and significant effect on purchase decisions, either partially or simultaneously, and together explain a substantial proportion of the variance in students' purchase decisions. These findings suggest that businesses targeting the student market need to encourage authentic user-generated content and design social media strategies that actively engage students in order to strengthen purchase decisions.